2017
DOI: 10.21037/atm.2017.03.106
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of epilepsy and acute pancreatitis induced by severe paraquat poisoning

Abstract: Paraquat can lead to injury of multiple organs. As there is no specific treatment for paraquat poisoning, it represents a serious clinical problem. Antioxidants are required to treat oxidative stress in paraquat poisoning and paraquat-induced injury. In this study, we report on successful treatment of a rare case of epilepsy and acute pancreatitis caused by paraquat poisoning. A 29-year-old woman at our hospital presented with a 13-day history of nausea and vomiting after ingesting 20 mL of paraquat (20% W/V).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Epilepsy and acute pancreatitis are also induced by ingesting 20 ml of PQ (20% W/V), which was related to PQ-produced OS or free radicals. 28 Nausea, vomiting, and a severe substernal burning sensation are indicated after accidental poisoning caused by ingesting approximately 100 ml of PQ (60% solution) concentration. 29 Nausea, vomiting, discomfort, and neutropenia were observed in a 15-year-old girl, who ingested a small quantity of wine full of PQ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy and acute pancreatitis are also induced by ingesting 20 ml of PQ (20% W/V), which was related to PQ-produced OS or free radicals. 28 Nausea, vomiting, and a severe substernal burning sensation are indicated after accidental poisoning caused by ingesting approximately 100 ml of PQ (60% solution) concentration. 29 Nausea, vomiting, discomfort, and neutropenia were observed in a 15-year-old girl, who ingested a small quantity of wine full of PQ.…”
Section: Discussionmentioning
confidence: 99%
“…49 In addition, epilepsy or convulsion was investigated in clinical case reports and studies. 28,29,50 Therefore, PQ-induced neurotoxicity is a matter of concern and should be prevented or treated in intoxicated patients. These findings indicated that PQ poisoning patients should be followed up for a long time after discharge from a hospital.…”
Section: Discussionmentioning
confidence: 99%